Perineum massage as the implementation of non-pharmacological method in pregnant women trimester III in efforts to prevent tearing perineum at Toroh Public Health Center I - Pintam Ayu Yastirin; Sehmawati Sehmawati (Alma Ata University Press, 2021)
Background : Incidence of maternal mortality in Central Java is 64.18% during the puerperium, 25.72% during pregnancy and 10.10% during childbirth. Of the 35 districts / cities in Central Java, Grobogan Regency was recorded as one of the districts with the most MMR (AKI) in 2019, amounting to 36 cases. Emergencies can occur during the puerperium which are often caused by bleeding, infection and pre-eclampsia. cases of bleeding during the puerperium are caused by major risk factors such as uterine atony (70%), lacerations of the birth canal (20%), retained placenta (10 - 20%) and coagulopathy (1%).hemorrhage Post partum due to perineal tearing can be minimized by improving the quality of service both promotive, preventive, curative and rehabilitative. One method of preventing perineal tearing can be done since pregnancy by performing perineal massage. Objectives : The purpose of this study was to determine the effectiveness of perineal massage in third trimester pregnant women as a non-pharmacological method in preventing perineal tears at Toroh I Health Center. Methods : The study used a pre-experimental design with amodel static group comparison, with a sample selected using a purposive sampling technique of 48 pregnant women. The research data used is in the form of primary data and secondary data. The research was analyzed using univariate and bivariate analysis using the test Fisher Exact Probability. Results : The results of the research were univariate analysis of 50% of respondents doing perineal massage, 58% of respondents did not experience perineal rupture, while the bivariate analysis of perineal massage variables and perineal rupture variables showed p-value <0.05 with OR: 18.142 at the 95% confidence level. Conclusions : There is a significant effect between perineal massage on the incidence of perineal rupture at Toroh Public Health Center I.